Modeling of Complex Interfaces: From Surface Chemistry to Nano Chemistry From Surface Chemistry to Nano Chemistry - Tielens, Frederik (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Introducing the interdisciplinary field of interface chemistry modelling across a wide range of academic disciplines and industry sectors. Ten original research articles are presented that bridge knowledge acquisition and practical work, providing a starting point for the research and development of applications. The book describes the characterization of interfaces at the nanoscale, using a wide range of key nanomaterials, such as graphene, TiO2, zeolites, semimetals, and organic polymers; and the study of their different physical chemical properties, such as catalysis, adsorption, friction, diffusion, and the characterization of nanocomposites and heterojunctions, with many different industrial applications. The resulting collection of papers is equally relevant for advanced students (senior and graduate) and for engineers and scientists from a variety of different academic backgrounds working in the multidisciplinary field of nanotechnology.